(untitled) - LoCascio, Ted (San Francisco,London, 2005)
If you're making the switch from QuarkXPress or PageMaker to Adobe InDesign or just starting out with page layout and design, InDesign CS2 at Your Fingertips is your ultimate reference. Its award-winning format gives you easy and instant access to all the tasks you'll want to perform. Author Ted LoCascio is a highly qualified instructor--he's the former senior designer for the National Association of Photoshop Professionals and an InDesign expert. With clear, accessible information and a full color section, this is the best value on the market
Keywords: Desktop publishing,Chế bản văn phòng